A portrait of the artist as a young man, by James Joyce - Wachtel, Albert (Pasadena, Calif. : Salem Press, 2012)
Collects critical essays on James Joyce's "A Portrait of the Artist as a Young Man" including selections by Jonathan Mulrooney, Albert Wachtel, Parker Douglas, and others; and includes a chronology of the life of the author.
On A portrait of the artist as a young man : beyond subjectivity -- the toddler Stephen theory and the quest for truth / Albert Wachtel -- A portrait of the artist as James Joyce : biography / Tara Prescott -- The Paris review perspective / Patrick Loughran for The Paris review -- An education in the unwholesome : dirt, stench, and desire in A portrait of the artist as a young man / Melissa Free -- The smithy of Stephen Dedalus's soul in A portrait of the artist as a young man : contexts for Joyce's novel / Maureen O'Connor -- Joyce, Byron, and the fall of seraphim / Albert Wachtel -- "By dint of brooding on the incident" : professional readers' responses to A portrait of the artist as a young man / Parker Douglas -- The cubist portrait / Hugh Kenner -- Epiphanies of Dublin / Richard M. Kain -- The woman of the Ballyhoura Hills : James Joyce and the politics of creativity / Marian Eide -- Joyce among the brothers / John W. Mahon -- The ordeal of Stephen Dedalus : the conflict of generations in James Joyce's A portrait of the artist as a young man / Edmund L. Epstein -- Stephen Dedalus and the chain of command / Albert Wachtel -- Stephen Dedalus and the politics of confession / Jonathan Mulrooney -- Silencing Stephen : colonial pathologies in Victorian Dublin / Tracey Teets Schwarze -- Refining the artist into existence : Pygmalion's statue, Stephen's villanelle, and the Venus of Praxiteles / Bonnie Roos -- Resources -- Chronology of James Joyce's life and times -- Works by James Joyce -- Bibliography.
Includes bibliographical references and index.
Keywords: Joyce, James, -- 1882-1941.; Dedalus, Stephen -- (Fictitious character); Young men in literature; Dublin (Ireland) -- In literature; A portrait of the artist as a young man; Aufsatzsammlung